Determinan Profitabilitas Asuransi Umum Syariah (Studi Kasus pada Perusahaan Asuransi Umum Unit Usaha Syariah yang Terdaftar di Otoritas Jasa Keuangan Periode 2019-2024) - Siti Rodiyah; Moh Mukhsin; Ahmad Fatoni (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
The purpose of this study is to empirically prove and examine the effect of financial ratios of volume of capital, investment returns, premium income, risk-based capital, underwriting results and operating costs on the profitability of general insurance companies of sharia business units registered with the financial services authority for the period 2019-2024. Profitability is measured by Return on Assets (ROA) and the method used in this study is quantitative with panel data types obtained from third parties (secondary). This study uses eleven samples of general insurance companies of sharia business units and uses panel data regression analysis techniques with the help of Eviews 10 software. The results show that volume of capital, investment returns, risk-based capital, underwriting results have a significant effect on profitability. Meanwhile, premium income and operating costs do not have a significant effect on profitability. This study provides implications that general sharia insurance companies need to pay attention to aspects of volume of capital, investment returns, risk-based capital and underwriting results and can consider the value of premium income and operating costs in supporting increased company profitability so that the performance of general sharia insurance becomes better.